Percutaneous Management of Pyogenic Liver Abscesses. Issue 4 (1989) - Helenon, O.; Krachte, M.; Mathieu, D.; Vasile, N.; Rotman, N.; Fagniez, P. –L.
Abstract : Twenty-four pyogenic liver abscesses have been treated during a six-year period percutaneously. Percutaneous management included percutaneous drainage and fine needle aspiration under ultrasound or CT scan guidance. Percutaneous management was successful in 92% of cases, and no further treatment was required in 91% of these. One patient died, giving a mortality rate of 4.1%. There were no complications related to this method. The authors conclude that percutaneous management of pyogenic liver abscesses should be attempted in all cases, since results compare favourably with surgical procedures.